PENDIDIKAN MITIGASI BENCANA PESISIR DAN LAUT BAGI SISWA SMA ANGKASA, KOTA AMBON - Tubalawony, Simon; Hiariey, Johanis; Retraubun, Alex S W; Siahainenia, Laura; Hukubun, Ronald D (Pattimura University, 2022)
The Maluku Province region has the potential and is prone to high threats of natural disasters. The condition of the area consisting of small islands requires the community to have knowledge of coastal and marine disaster mitigation, so that it will increase awareness and minimize the impact when a disaster occurs. There are several stages in the implementation of PKM, including initial survey, coordination, problem identification, PKM implementation and counseling. Through this PKM, it has increased the understanding of the public (Angkasa high school students) to be more alert and alert to the potential vulnerability of coastal and marine disasters which can occur at any time